Pengaruh Religiusitas, Atribut Produk Islam, dan Kualitas Pelayanan terhadap Minat Menabung Anggota di KSPPS KAS Kocika Artha Sejahtera Jepara - Mahmudatus Sa'diyah; Anggi Azyaniz Zumala (JIOSE: Journal of Indonesian Sharia Economics, 2026)
This study aims to analyze the influence of religiosity, Islamic product attributes, and service quality on members’ saving interest at KSPPS KAS Kocika Artha Sejahtera. This research employs a quantitative approach with a sample of 98 respondents selected using a simple random sampling technique based on the Slovin formula. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that partially, religiosity, Islamic product attributes, and service quality each have a positive and significant effect on members’ saving interest. Religiosity has a significant positive effect with a t-value of 6.628 and a significance level of 0.000. Islamic product attributes also have a significant positive effect with a t-value of 2.483 and a significance level of 0.030. Meanwhile, service quality shows a significant positive effect with a t-value of 4.220 and a significance level of 0.000. Simultaneously, the three independent variables have a significant effect on saving interest, as indicated by an F-value of 48.478 with a significance level of 0.000. The coefficient of determination (R²) is 0.607, indicating that 60.7% of the variation in saving interest can be explained by the three independent variables, while the remaining 39.3% is influenced by other factors outside the research model.